ANALYSIS OF THE COVID-19 VACCINATION CIRCULAR FOR SCHOOLCHILDREN ON THE INSTAGRAM ACCOUNT @INFOSUMBAR - Fitriyani, Fitriyani; Rahmat, Wahyudi; Samsiarni, Samsiarni (Journal of Humanity Studies, 2022)
This research is motivated by comments on vaccination circulars uploaded to the Instagram account @InfoSumbar so that it can be seen from the expressiveness of language conveyed by speakers in the comments column through their language acts which use a lot of expressive speech acts. This research will be discussed in a pragmatic study, where expressive speech acts are conveyed through the Instagram comment column, which is seen from the speech delivered by the speaker according to his thoughts. This approach examines expressive speech acts that are motivated by expressing one's feelings when one wants to convey their thoughts. The type of research used in this research is qualitative research. The data in this study are expressive speech acts in the comments column of the Covid-19 vaccination circular for school children on the Instagram account @InfoSumbar in the form of sentences and words. The data source used is the posting of circulars on Instagram @InfoSumbar. Data were collected by listening and note-taking techniques. The data were analyzed by the distribution method. Based on the study's results, it was found in the speech in the comment column of the Covid-19 vaccination circular for school children on the @InfoSumbar Instagram account. Was used as a data source; there were four forms of action, namely speech acts of difficulty, joy, hatred, and misery.